2D/2D GO-modified g-C3N4 nanocomposite for efficient photocatalytic CO2 reduction to CH4 under visible light - Ikreedeegh, Riyadh Ramadhan; Hossen, Md Arif; Tahir, Muhammad (Libyan Center for Solar Energy Research and Studies, 2024)
Polymeric graphitic phase carbon nitride (g-C3N4) photocatalysts offer significant potential for CO2photoreduction into solar fuels despite their efficiency restricted due to poor light response and recombination of photo-generated charges. This study focused on the modification of g-C3N4by single-layered graphene oxide (GO) for enhancing photocatalytic CO2reduction activity to form CH4. Well-designed 2D/2D GO-g-C3N4was fabricated using facile thermal strategy. The hybrid photocatalyst exhibited improved CO2photoreduction performance to produce CH4. The maximum CH4yield of 25.61 µmol g-1 was achieved after 4 h of visible light illumination which represents about 25% enhancement compared to pristine g-C3N4.